Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1128/jvi.00384-15
|View full text |Cite
|
Sign up to set email alerts
|

Murine Immune Responses to Virus-Like Particle-Associated Pre- and Postfusion Forms of the Respiratory Syncytial Virus F Protein

Abstract: Virus IMPORTANCEThe development of vaccines for respiratory syncytial virus has been hampered by a lack of understanding of the requirements for eliciting high titers of neutralizing antibodies. The results of this study suggest that particle-associated RSV F protein containing mutations that stabilize the structure in a prefusion conformation may stimulate higher titers of protective antibodies than particles containing F protein in a wild-type or postfusion conformation. These findings indicate that the pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 48 publications
4
69
1
Order By: Relevance
“…Although others have shown that two doses of prefusion F, either as a soluble protein (32) or incorporated into VLPs (52), can induce protection against RSV challenge in rodent models of RSV infection, our results indicate that at low antigen concentrations, individuals may remain susceptible to infection following the first vaccination and before the second dose has been administered. However, in aggregate, prefusion F is capable of inducing the highest levels of neutralizing antibodies after a single dose and conferring protection with minimal pathology at high doses of the immunogen.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although others have shown that two doses of prefusion F, either as a soluble protein (32) or incorporated into VLPs (52), can induce protection against RSV challenge in rodent models of RSV infection, our results indicate that at low antigen concentrations, individuals may remain susceptible to infection following the first vaccination and before the second dose has been administered. However, in aggregate, prefusion F is capable of inducing the highest levels of neutralizing antibodies after a single dose and conferring protection with minimal pathology at high doses of the immunogen.…”
Section: Discussionmentioning
confidence: 67%
“…The reasons for this disparity are unknown, but it is worth stressing that proteins with essentially identical primary structures may induce significantly different antibody responses depending on their conformations. A relatively similar preference for prefusion-specific antibodies was recently reported for mice inoculated with Newcastle disease virus-like particles (VLPs) that incorporated engineered prefusion hRSV F (52).…”
Section: Discussionmentioning
confidence: 84%
“…The high capacity of pre-F to elicit neutralizing antibody titres has been demonstrated in multiple vaccine platforms, including purified proteins121314, virus-like particles15, and recombinant parainfluenza viruses16. Use of pre-F in passive immunization, either by anti-pre-F monoclonal antibody (mAb) prophylaxis or by boosting RSV neutralizing antibody (nAb) titres in pregnant mothers with pre-F protein-based vaccines, holds promise for reducing RSV disease in the youngest infants14.…”
mentioning
confidence: 99%
“…Thus, fine tuning of changes introduced in chimeric proteins may be critical for their expression and immunogenicity. The use of other expression systems or incorporation of chimeric proteins into viral vectors (Liang et al , 2017) or virus particles (McGinnes et al , 2015) are alternatives to improve production and/or immunogenicity of chimeric F proteins. Nonetheless, the results presented here represent a proof of principle to design chimeric proteins that may be used as single immunogens to induce cross‐neutralizing and cross‐protecting immune responses against the important Pneumoviridae members, hRSV and hMPV.…”
Section: Discussionmentioning
confidence: 99%